The meaning and value of freedom: Berlin contra Arendt - Hiruta, K (Routledge, 2014)
This essay considers the theoretical disagreement between Isaiah Berlin and Hannah Arendt on the meaning and value of freedom. Berlin thinks that negative liberty as non-interference is commendable because it is attuned to the implication of value pluralism that man is a choice-making creature and cannot be otherwise. By contrast, the political freedom to act is in Arendt’s view a more fulfilling ideal because it is only in political action that man’s potentiality is actualised, his unique identity manifested and his being-in-the-world-with-others reaffirmed. What lies beneath the two thinkers’ dispute over the most satisfactory meaning of freedom, I argue, is a deeper disagreement over human nature itself. The implication of this analysis for the contemporary debate between pluralist liberals and their agonistic critics is briefly discussed in conclusion.